Experimental Research of Influence of Oil-air Lubrication on Temperature Characteristic of Mechanical Spindle - Xie Pei; Zhu Rupeng; Li Miaomiao; Yang Yang (Jixie chuandong)
In order to study the temperature characteristics of mechanical spindle,a mechanical spindle platform using oil-air lubrication is developed. The evaluation criterion of temperature characteristics is proposed. The experiments of influence of oil quantity per hour and air pressure on temperature rise and distribution are conducted. The results show that oil quantity per hour weights the most in temperature performance of mechanical spindle among all oil-air lubrication parameters while air pressure is second to it,the interaction between these two parameters hardly influences the temperature performance. The best oil quantity per hour is0. 1 m/h under 8 000 r/min. The increase or decrease of the best oil quantity per hour tends to lead to larger increase of temperature rise,the increase of air pressure in oil-air lubrication tends to lead to a lower temperature rise in mechanical spindle.